2012
DOI: 10.1111/j.1365-2710.2012.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of micafungin and voriconazole in the treatment of invasive fungal infections in kidney transplant recipients

Abstract: This is the first comparison of micafungin and voriconazole in renal transplant patients. Our study shows that the effectiveness of micafungin was similar to that of voriconazole in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
1
11
0
1
Order By: Relevance
“…However, there were significantly positive outcomes for the prevention model [35]. Our pooled analysis of 9 RCTs with a total of 2,008 patients confirmed that MCFG had a higher treatment success rate for the prevention model, but not for the empiric treatment model.…”
Section: Discussionmentioning
confidence: 62%
“…However, there were significantly positive outcomes for the prevention model [35]. Our pooled analysis of 9 RCTs with a total of 2,008 patients confirmed that MCFG had a higher treatment success rate for the prevention model, but not for the empiric treatment model.…”
Section: Discussionmentioning
confidence: 62%
“…Among all of the included trials, six studies [ 20 , 22 26 ] were related to the treatment of proven/probable fungal infections, while four studies [ 21 , 27 29 ] were involved in the prophylaxis for high risk of fungal infections. One trial compared caspofungin with fluconazole [ 20 ], one trial compared caspofungin with itraconazole [ 21 ], one trial compared anidulafungin with fluconazole [ 22 ], four trials compared micafungin with fluconazole [ 23 , 24 , 27 , 29 ], two trials compared micafungin with voriconazole [ 25 , 26 ], and one trial compared micafungin with itraconazole [ 28 ]. In terms of methodology, all of the included trials were deemed to be of good quality according to the Jadad score (≥2), with nine trials being multicenter randomized and double-blinded, and the last being randomized and open-labeled.…”
Section: Resultsmentioning
confidence: 99%
“…50 mg q.d. Itraconazole: oral 5 mg/kg/day (in two administrations) 287 136/137 3 Shang et al, 2012 [ 25 ] Multicenter, open-label RCT Kidney transplant recipients with IFI Micafungin: i.v. 100 mg/day (<60 kg) or 150 mg/day (>60 kg) Voriconazole: i.v.…”
Section: Resultsmentioning
confidence: 99%
“…But its use is very limited now-a-days due to its severe side effects such as electrolyte disturbances and nephrotoxicity. 4,5 Many antifungal agents are available during the past 25 years with broad spectrum antifungal activity. Voriconazole is one of the second generation synthetic triazole with broad spectrum antifungal activity and is available in oral and intravenous formulations.…”
Section: Introductionmentioning
confidence: 99%